Pengaruh Harga dan Kualitas Pelayanan terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan sebagai Variabel Intervening (Studi pada Pelanggan Indihome PT Telekomunikasi Indonesia, Tbk. (Persero) Semarang - Noni Permata Sari; Agung Budiatmo (Universitas Diponegoro, 2019)
To ensure the continuity of business, a company should attempt to maintain customer's loyalty. maintaining customer's loyatly is not as easy as it looks, one of factor that influence the customer's loyalty is customer satisfaction. customer's satisfaction play an important role to maintain a continuity of business so it can face the rivalry. there are some factors to shape customer's satisfaction and create customer's loyalty. price is one amongst them, where a suitable price with its advantages can create customer's satisfaction and so followed by customer's loyalty. beside price, a good service quality or as what customer expect can also create customer's satisfactiom. The purpose of this research is to determine the effect of price and service quality to consumer loyalty through customer satisfaction of PT Telekomunikasi Indonesia customers. the sample of this research is 100 respondents with purposive sampling approach technique. data analysis method that been used are validity test, reliability test, correlation coefficient, coefficient of determinant, simple and multiple regressionsignificance test (T test and F test) using SPSS version 21.0 and Sobel Test with Preacher Tool. The results of this study indicate that the price category of 48% is appropriate. Service quality category known as 58% stated good. The customer satisfaction category known as 40% is satisfied. Categorization of customer loyalty is known by 47% is loyal. From the data analysis results, it is known that price and service quality have a significant influence on customer satisfaction and customer loyalty variables. Price variables that affect customer loyalty through customer satisfaction occur full mediation (full mediation) and a variable service quality that is affect customer loyalty through customer satisfaction occurs partial mediation (partial mediation). Suggestions that can be given is that PT. Telekomunikasi Indonsia Semarang is promoting the advantages of IndiHome products from other broadband, accelerating employees in handling problems faced by customers, employees prioritizing customer interests by better understanding customer desire.